Avaliação parcial do índice de mobilidade urbana sustentável do município de Alegrete - RS - Furraer, Igor Leonardo Loeblein (2017)
This study aims to evaluate, in part, the situation of urban mobility in the city of Alegrete-RS,throughout the sustainability view. The evaluation will be done through the Index of Sustainable Urban Mobility (I_SUM). I_SUM has been shown to be a very complete tool for investigating the situation of urban mobility in Brazilian cities and has been applied in several locations with in the country. This tool is composed of nine Domains, thirty-seven Themes and eighty-seven Indicators. In order to measure the urban mobility of acertain locality, it is necessary to evaluate the Indicators, which will composse the grade of their respective Themes, and those are responsible for the score of each of the Domains. The sum of the grades of all Domains will composse the over all rating of the city accordingly to sustainable urban mobility. There fore, I_SUM has a hierarchical structure, which e nables not only to measure the global score of sustainable urban mobility of a town, but also can show the strength sand weaknesses of sustainable urban mobility in a city. As a result, the I_SUM enables the Administrative Centers to have agreater sense of critical points that need bigger investments. The application of I_SUM in Alegrete-RS allowed the identification of important aspects about the mobility situation in the town. Evaluating part of the indicators, the city reached a score of 0.614in the I_SUM tool, which is considered good according to the evaluation scale proposed for the index. However, it is necessary to continue evaluating other indicators in order to conceive a better idea of the over all mobility situation for the city. Evaluating Indicators which obtained a lower score than the partial scorer eached by the town, it be came possible to identify indicators which have good expectations for improvement. Therefore, these are potential áreas to receive actions promoting sustainable urban mobility.